2018
DOI: 10.1093/jxb/ery054
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium intensifies CAM photosynthesis and counteracts drought effects by increasing malate transport and antioxidant capacity in Guzmania monostachia

Abstract: Leaves of Guzmania monostachia exposed to ammonium and water deficit showed increased CAM photosynthesis and water deficit tolerance by increasing vacuolar malate channel expression levels, antioxidant enzyme activities, and soluble sugar accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 64 publications
1
22
1
1
Order By: Relevance
“…Several studies have confirmed that the activity of superoxide dismutase (SOD) and ascorbate peroxidase (APX), as well as the concentrations of hydrogen peroxide (H 2 O 2 ) are up‐regulated during the induction of CAM (Ślesak et al 2008, Nosek et al 2015). Furthermore, antioxidant enzymes activities exhibit differential diurnal rhythm during C 3 ‐CAM transition (Niewiadomska et al 2011, Habibi and Hajiboland 2012, Pereira et al 2018). In a previous study, it has been reported that the C 3 ‐CAM transition can induce the changes in antioxidative enzymes activities in a reversible manner (Nosek et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed that the activity of superoxide dismutase (SOD) and ascorbate peroxidase (APX), as well as the concentrations of hydrogen peroxide (H 2 O 2 ) are up‐regulated during the induction of CAM (Ślesak et al 2008, Nosek et al 2015). Furthermore, antioxidant enzymes activities exhibit differential diurnal rhythm during C 3 ‐CAM transition (Niewiadomska et al 2011, Habibi and Hajiboland 2012, Pereira et al 2018). In a previous study, it has been reported that the C 3 ‐CAM transition can induce the changes in antioxidative enzymes activities in a reversible manner (Nosek et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to Han et al [70], under low temperature stress, the content of NO 3 --N and the NR activities in tomato leaves signi cantly decreased, while the NH 4 + -N content signi cantly increased. Under drought stress, the NH 4 + nutrition can limit the effect of water de cit by osmotic adjustment and can limit oxidative damage [71].…”
Section: Different Changes Of Nrt and Amt Family Gene Expression Pattmentioning
confidence: 99%
“…The influence of NO 3 − on CAM expression has been documented in several obligate and facultative CAM species [43,45,70,71,72]. Researchers observed that K. blossfeldiana plants grown under 1 mM NO 3 − or NH 4 + despite having the same growth rates, showed higher nocturnal CO 2 uptake and nocturnal malate content in the presence of NO 3 − [70].…”
Section: Relationship Between Nitrogen and Cammentioning
confidence: 99%
“…, when G. monostachia was grown in the presence of 5.0 mM NO 3 − and exposed to water-deficit stress, the magnitude of CAM decreased by lowering nocturnal malate and citrate accumulation, PEPC and MDH activities, GmoALMT9 expression (aluminum-dependent malate transporter), and the rates of ATP and PPi-dependent proton transport when compared to plants grown in the presence of 5.0 mM NH 4 + and water-deficit stress. When lower concentrations of NO 3 − were evaluated (e.g., 1.25 mM and 2.5 mM), a slight increase in PEPC activity was observed; however, it was still lower than when compared to the same concentrations of NH 4 + [72]. Thus, the preference for each N source seems to depend upon the plant species, their habitat, and the relative toxicity of the N source for the plant.…”
Section: Relationship Between Nitrogen and Cammentioning
confidence: 99%